Optimization and Adsorption-Based Recovery of Cobalt Using Activated Disordered Mesoporous Carbons - I. Bernabé; J.M. Gómez; E. Díez; P. Sáez; A. Rodríguez (Advances in Materials Science and Engineering)
Kinetic and operating condition studies were studied in the batch mode. MCSG60A has a large and fast adsorption capacity, retaining 90% of the Co2+ in the solution and reaching equilibria in only 15 minutes. Among all the variables studied, the adsorbent dosage and the agitation speed favor the Co2+ adsorption until an agitation speed of 1100 rpm and 15.0 mg/L of adsorbent dosage; higher values do not increase the adsorption capacity. On the other hand, the presence of Na+ ions in the solution and high particle size hinder the adsorption process. The thermodynamic study indicated that this process is exothermic and spontaneous, mainly caused by electrostatic interactions between adsorbent and adsorbate. The adsorption is highly pH dependent: while it is optimum at basic pH, it decreases by a 70% at pH 2. The adsorption process is favored in controlled pH, in spite of the ionic strength that involves the buffer presence in the solution. As to the cobalt recovery, to preconcentrate this metal, it is tested with different acid solutions, proving that lower pH promotes this phenomena, even reaching a recovery around 98%, with HNO3 solution with 0.5 pH. Moreover, if the volume of regenerative solution is decreased to the eight part, the cobalt concentration increases five times, reaching enough concentration to facilitate its recovery in metallic state by other techniques.